Vector time series models for prediction of air quality inside a public transportation bus using available software. Issue 4 (6th September 2014) - Kadiyala, Akhil; Kumar, Ashok
<x xml:space="preserve">Abstract</x> Development of practical in‐vehicle air quality vector time series models is useful for examining new (or enhancement of existing) control strategies for managing indoor air quality (IAQ) within the considered transit microenvironment. The models are helpful to the vehicle manufacturers in understanding the scope for preventing in‐vehicle contaminant concentration buildup beyond permissible IAQ guidelines, and to the commuters in understanding the risks of exposure to various air contaminants. This study demonstrates the methodology to develop and validate the vector time series models (VARMA/VARMAX) for the in‐bus contaminant concentrations of carbon dioxide and carbon monoxide using available software. © 2014 American Institute of Chemical Engineers Environ Prog, 33: 1069–1073, 2014